Upgrading biomass-derived furans via acid-catalysis/hydrogenation: the remarkable difference between water and methanol as the solvent† - Hu, Xun; Westerhof, Roel; Wu, Liping; Dong, Dehua; Li, Chun-Zhu (The Royal Society of Chemistry, 2015)
In methanol 5-hydroxymethylfurfural (HMF) and furfuryl alcohol (FA) can be selectively converted into methyl levulinate via acid-catalysis, whereas in water polymerization dominates. The hydrogenation of HMF, furan and furfural with the exception of FA is much more selective in methanol than in water.